Novel Reassortant Avian Influenza A(H9N2) Virus Isolate in Migratory Waterfowl in Hubei Province, China - Li, Xiang; Sun, Jing; Lv, Xinru; Wang, Yajun; Li, Yulei; Li, Minghui; Liu, Wei; Zhi, Min; Yang, Xiaoyu; Fu, Tian; Ma, Peiran; Li, Yi; et al. (Frontiers in Microbiology, 2020)
In December 2017, an influenza A(H9N2) virus (B51) was isolated from migratory waterfowl in Hubei Province, China. Phylogenetic analysis demonstrated that B51 is a novel reassortant influenza virus containing segments from human H7N4 virus and North American wild bird influenza viruses. This suggest that B51 has undergone multiple reassortment events.